
已知(-a+b+c)/a=(-b+a+c)/b=(-c+b+a)/c=k,则k=
1个回答
展开全部
答:
(-a+b+c)/a=(-b+a+c)/b=(-c+b+a)/c=k
-a+b+c=ka
-b+a+c=kb
-c+b+c=kc
三式相加得:
2(a+b+c)-(a+b+c)=k(a+b+c)
a+b+c=k(a+b+c)
(k-1)(a+b+c)=0
k-1=0或者a+b+c=0
所以:k=0
a+b+c=0时:-a=b+c
所以:k=(-a+b+c)/a=(-a-a)/a=-2
综上所述,k=1或者k=-2
(-a+b+c)/a=(-b+a+c)/b=(-c+b+a)/c=k
-a+b+c=ka
-b+a+c=kb
-c+b+c=kc
三式相加得:
2(a+b+c)-(a+b+c)=k(a+b+c)
a+b+c=k(a+b+c)
(k-1)(a+b+c)=0
k-1=0或者a+b+c=0
所以:k=0
a+b+c=0时:-a=b+c
所以:k=(-a+b+c)/a=(-a-a)/a=-2
综上所述,k=1或者k=-2
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询